Adrenocorticotropic hormone-independent hypercortisolism managed by bilateral retroperitoneoscopic adrenalectomy: Report of a case and review of literature - M M Zameer; Sanjay Rao; C Vinay; Ashley D'Cruz (Wolters Kluwer Medknow Publications, 2022)
Bilateral adrenalectomy is the reference treatment for Cushing's syndrome related to adrenocorticotropic hormone-independent macronodular adrenal hyperplasia (AIMAH). We report a case of AIMAH managed by sequential retroperitoneoscopic adrenalectomy and review the literature of the same.